Home » make U the subject of the formula S = (sqrt{frac{6}{u} – frac{w}{2}})

make U the subject of the formula S = (sqrt{frac{6}{u} – frac{w}{2}})

make U the subject of the formula S = (sqrt{frac{6}{u} – frac{w}{2}})
  • A.
    u = (frac{12}{2s^2})
  • B.
    u = (frac{12}{2s+ w})
  • C.
    u = (frac{12}{2s^2 + w})
  • D.
    u = (frac{12}{2s^2}) + w
Correct Answer: Option C
Explanation

S = (sqrt{frac{6}{u} – frac{w}{2}})
S = (frac{12 – uw}{2u})
2us2 = 12 – uw
u(2s2 + w) = 12
u = (frac{12}{2s^2 + w})